The packages clustering optimisation in the logistics of the last mile freight distribution. (2016) - Cepolina, Elvezia M.
The paper refers to the modelling and simulation of an innovative urban freight distribution scheme. Packages destined for receivers in an urban area are firstly delivered to the urban distribution centre (UDC); each package is characterised by an address and dimensions. The load units are consolidated in the UDC with packages. Each load unit is addressed to a temporary unloading bay, where receivers are after in charge of collecting their packages. The paper concerns a methodology for the load units consolidation which minimises the overall distance travelled by receivers, taking into account the load unit capacity and the maximum walking distance the receivers accept to collect their packages. A fuzzy k-means clustering algorithm has been adopted. The fuzzy clustering algorithm is recalled by a simulation model of the proposed transport system. The methodology has been applied to the case study of the historic city centre of Genoa, Italy.